2023
DOI: 10.3390/cells12060837
|View full text |Cite
|
Sign up to set email alerts
|

Broad Serotonergic Actions of Vortioxetine as a Promising Avenue for the Treatment of L-DOPA-Induced Dyskinesia

Abstract: Parkinson’s Disease (PD) is a neurodegenerative disorder characterized by motor symptoms that result from loss of nigrostriatal dopamine (DA) cells. While L-DOPA provides symptom alleviation, its chronic use often results in the development of L-DOPA-induced dyskinesia (LID). Evidence suggests that neuroplasticity within the serotonin (5-HT) system contributes to LID onset, persistence, and severity. This has been supported by research showing 5-HT compounds targeting 5-HT1A/1B receptors and/or the 5-HT transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Since the negative feedback inhibition resulting from the activation of 5‐HT1A autoreceptors plays a key role in the delay of antidepressant onset, it is possible to relieve the negative feedback inhibition caused by the activation of presynaptic 5‐HT receptors if antidepressants with both 5‐HT re‐uptake inhibitory and presynaptic 5‐HT receptor antagonistic functions can be developed, achieving the goal of fast efficacy (Fleischman et al, 2023; Zhou et al, 2023). Research has shown that a combination of 5‐HT receptor antagonist WAY‐100635 and selective serotonin reuptake inhibitor (SSRIs) can relieve SSRIs' inhibitory effect against the 5‐HT neuronal firing, and significantly enhance the SSRIs‐induced elevation of 5‐HT level in synaptic clefts (Budrow et al, 2023). Given the current lack of selective 5‐HT1A autoreceptor antagonists, the non‐selective 5‐HT antagonists may block both the pre‐ and postsynaptic 5‐HT1A receptors to cancel the antidepressant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Since the negative feedback inhibition resulting from the activation of 5‐HT1A autoreceptors plays a key role in the delay of antidepressant onset, it is possible to relieve the negative feedback inhibition caused by the activation of presynaptic 5‐HT receptors if antidepressants with both 5‐HT re‐uptake inhibitory and presynaptic 5‐HT receptor antagonistic functions can be developed, achieving the goal of fast efficacy (Fleischman et al, 2023; Zhou et al, 2023). Research has shown that a combination of 5‐HT receptor antagonist WAY‐100635 and selective serotonin reuptake inhibitor (SSRIs) can relieve SSRIs' inhibitory effect against the 5‐HT neuronal firing, and significantly enhance the SSRIs‐induced elevation of 5‐HT level in synaptic clefts (Budrow et al, 2023). Given the current lack of selective 5‐HT1A autoreceptor antagonists, the non‐selective 5‐HT antagonists may block both the pre‐ and postsynaptic 5‐HT1A receptors to cancel the antidepressant effect.…”
Section: Discussionmentioning
confidence: 99%